Imaging of Laser Therapy in Epilepsy. Issue 3 (29th March 2017) - Nagae, Lidia M.; Honce, Justin M.; Nyberg, Eric; Ojemann, Steven; Abosch, Aviva; Drees, Cornelia N.
ABSTRACT: BACKGROUND AND PURPOSE: MR‐guided laser interstitial thermal therapy (MRgLITT) is an increasingly popular neuroablative method for the surgical treatment of epilepsy patients. This article intends to demonstrate the utility and pitfalls of imaging in the context of patient care with MRgLITT. MATERIAL AND METHODS: A retrospective review of the medical records and imaging database with six illustrative cases selected to demonstrate the use of imaging throughout patient management with MRgLITT in diverse clinical situations and pathologies. A review of the knowledge in the literature was applied to the relevant points discussed. RESULTS: Imaging findings were described in the setting of laser therapy in nonlesional epilepsy, mesial temporal sclerosis, dual pathology, periventricular nodular heterotopia, and schizencephaly. Discussion of imaging principles, potential pitfalls, as well as its use in the patient work‐up and follow‐up, is shown. CONCLUSIONS: MRgLITT is an alternative minimally invasive therapy for refractory epilepsy, which is becoming widely sought for. Imaging plays a crucial role prior to, during, and after the procedure.